IMPLEMENTATION OF THE SHIP FOR SOUTHEAST ASIAN AND JAPANESE YOUTH PROGRAM (SSEAYP) TO IMPROVING MUTUAL UNDERSTANDING BETWEEN INDONESIA-JAPAN IN 2018-2019 - Revana Puti Ramadhan; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study was written to find out how the implementation of The Ship for Southeast Asian and Japanese Youth Program (SSEAYP) to improve friendship and mutual understanding between Indonesia-Japan. SSEAYP is an important mechanism and a pioneering project for Japan that can help improve the country's negative image from the perception of countries in Southeast Asia, SSEAYP is also used by Japan as public diplomacy to create mutual understanding and sustainable relations between Japan and ASEAN countries. For Indonesia, SSEAYP provides an opportunity to promote Indonesian culture and state through its youth conducting cultural diplomacy with Japan and other ASEAN countries as well as assisting the process of preparing a cadre of future Indonesian leaders.This study uses the theory of public diplomacy with a globalization perspective. The research method used in this research is the explanation with the qualitative research type. The data collection technique of this research is analyzing documents from various information collected through books, journals, theses, articles, and news as well as other related documents via the internet.The research show that the implementation of SSEAYP to improve friendship and mutual understanding between Indonesia-Japan is realized through cultural exchange activities and dicussion programs that carried out by participating youths while participating in the onboard activity and country programs. The program has been successful in achieving its proven objectives by continued implementation of SSEAYP activities to date and the evaluation of participants who claim that SSEAYP has contributed to promoting friendship and mutual understanding among people from other countries. Keywords: Public Diplomacy, SSEAYP, Indonesian-Japan Relation.